Enigma of Fixed Retainers - Eapen, Jijo C; Prakash, Amit (Orthodontic Journal of Nepal, 2017)
Fixed retainers are a reliable form of retention for avoiding relapse and maintaining dental arch shape. They function regardless of patient cooperation, and they fulfill high esthetic expectations. Teeth have tendency to return to their former position, as time required for retaining the treatment result. The most appropriate mode of retention for the post-treatment situation should be used, based on a careful evaluation of the patient’s pretreatment diagnostic records, habits, cooperation, growth pattern, and age. Retention after orthodontic intervention is as important part of the therapy as the active treatment. Age and maturity of the patients, result of the orthodontic intervention, origin and character of the anomaly, type of the retainer, compliance of the patients; all can influence the chance of relapse. The retention period should be twice longer than the active orthodontic treatment. This article covers various aspect of fixed retention in detail